The Scope of Authority of The Acting Regional Head Due to The Victory of The Empty Column in The Regional Elections - St. Hartina; Hernadi Affandi; Inna Junaenah (CV. Syntax Corporation Indonesia, 2024)
The victory of the Blank Column in the Regional Elections has an impact on the appointment of the Acting Regional Head to run the regional government until the election of the Regional Head in the next Regional Election. The Acting Regional Head is given the task of replacing the definitive Regional Head but there are differences in its application. In this paper, the scope of authority of the Acting Regional Head is discussed using normative juridical research with a statutory approach or statute approach and a conceptual or conceptual approach or conceptual or conceptual approach or conceptual acceptal acpproach. The results of this study show that juridically assigning tasks to the Acting Regional Head is inconsistent and hinders the course of regional autonomy. This paper also discusses alternative arrangements for the Acting Regional Head to be in line with the principle of regional autonomy.